Stomata cells studies of Paraphalaenopsis spp. from in vitro and greenhouse condition - R. VITRI GARVITA; Hary Wawangningrum (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Garvita RV, Wawangningrum H. 2020. Stomata cells studies of Paraphalaenopsis spp. from in vitro and greenhouse condition. Biodiversitas 21: 1116-1121. In vitro micropropagation is an efficient biotechnological strategy for conservation and commercial plantlet production. The ultimate success of in vitro microporapagation depends on the ability to transfer plants out of culture, known as acclimatization stage. The morphology, anatomy and physiology of plantlets in in vitro culture conditions is different from the plants in environment condition (greenhouse), therefore they are unable to compete with soil microbes and to cope with the environmental conditions. The aim of this research is to determine stomata morphology and distribution of Paraphalaenopsis spp (Orchidaceae) from in vitro growth and greenhouse conditions. The leaf stomata cells of Paraphalaenopsis spp. (Paraphalaenopsis serpentilingua, Paraphalaenopsis labukensis and Paraphalaenopsis laycockii) was undertaken by observing the stomata preparation of the upper leaf and lower leaf by using microscope fitted with optic visual seven. The descriptive method was used to describe the stomata morphology by observing the epidermis of longitudinal section and stomata length of upper and lower leaf by using a microscope. The results showed that these plants had anomocytic type of stomata cells. The distributions of stomata are in the upper and lower epidermis leaf in all Paraphalaenopsis spp from in vitro growth and greenhouse.